Определение экономической эффективности применения современных компьютерных тренажеров при обучении эксплуатации бронетанковой техники - Бондарь, А. И.; Гужва, Ю. М.; Дегтярь, С. М.; Магерамов, Л. К.-А.; Смоляков, В. А. (НТУ "ХПИ", 2010)
In article components of annual economic benefit of application of modern computer training apparatus are defined at training of operation of armored technics, influence of each of them on numerical value o f annual economic benefit, mathematical expression of calculation of annual economic benefit is received.
Keywords: сухопутные войска; компьютерный тренажер; бронетанковая техника; бронетранспортер; компьютерные средства обучения; экономический эффект; обучение экипажа; эксплуатация бронетанковой техники